2019
DOI: 10.1038/s41467-019-11406-3
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of a core regulon by transposable elements promotes Arabidopsis chemical diversity and pathogen defense

Abstract: Plants synthesize numerous ecologically specialized, lineage-specific metabolites through biosynthetic gene duplication and functional specialization. However, it remains unclear how duplicated genes are wired into existing regulatory networks. We show that the duplicated gene CYP82C2 has been recruited into the WRKY33 regulon and indole-3-carbonylnitrile (ICN) biosynthetic pathway through exaptation of a retroduplicated LINE retrotransposon ( EPCOT3 ) into an enha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 76 publications
6
75
0
Order By: Relevance
“…For instance, a Hopscotch LTR retrotransposon regulates the domestication gene tb1 in maize through a long-range interaction [56,4]. In A. thaliana, LINE EPCOT3 is involved in the neo-functionalization of the Cyp82c2 gene, thus contributing to chemical diversity and pathogen defense [17]. In Brassica napus, a CACTA transposon acts as an enhancer to stimulate expression of the BnaA9.CYP78A9 gene and silique elongation [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a Hopscotch LTR retrotransposon regulates the domestication gene tb1 in maize through a long-range interaction [56,4]. In A. thaliana, LINE EPCOT3 is involved in the neo-functionalization of the Cyp82c2 gene, thus contributing to chemical diversity and pathogen defense [17]. In Brassica napus, a CACTA transposon acts as an enhancer to stimulate expression of the BnaA9.CYP78A9 gene and silique elongation [19].…”
Section: Discussionmentioning
confidence: 99%
“…Transposable Elements (TEs) of various superfamilies have been proposed as a source of new regulatory elements [15] and have been shown to be involved in the rewiring of gene regulatory networks for some key tissue-specific biological functions in animals [16]. In plants, examples of enhancers derived from a particular TE have been described [17,18,19], and a more general contribution of TEs to cis-regulatory elements has been highlighted in some species such as Capsella grandiflora [20] and maize, where at least a quarter of the thousands of putative enhancers were found to overlap TE annotations [8,10]. TEs influencing the response of nearby genes to abiotic stresses have also been described, for example in maize seedlings [21], hinting for an important role of TEs in regulating the expression of genes involved in specific biological functions in plants.…”
mentioning
confidence: 99%
“…As a technical control, we additionally included the indole GSL hydrolysis-impaired pen2 mutant, which over-accumulates defense-induced 4OH-I3M and 4M-I3M (Bednarek et al, 2009;Clay et al, 2009). We previously have shown that levels of 4M-I3M and its immediate precursor 4OH-I3M were increased at the expense of the parent metabolite I3M in Psta-infected WT plants compared to uninfected WT or Psta-infected rpm1 mutant, which is ETI-deficient when elicited with Psta (Bisgrove et al, 1994;Barco et al, 2019b). By contrast, I3M and 4OH-I3M levels were reduced in the Psta-infected myb51 mutant relative to Psta-infected WT ( Figure 2B), consistent with a previous report of reduced flg22-elicited indole GSL biosynthesis in myb51 (Clay et al, 2009).…”
Section: Myb51 and Myb122 Are Necessary For 4oh-i3m And 4m-i3m Biosynmentioning
confidence: 99%
“…PTI depends on signaling networks that identify the non-self microbial invader via its conserved microbe-associated molecular pattern molecules (MAMPs), whereas ETI utilizes pathogen-specific virulence effector proteins for pathogen detection (Jones and Dangl, 2006). Specialized metabolism is further dependent on gene regulatory networks (GRNs) that respond to perceived threats by activating defense-responsive transcription factors (TFs) (Clay et al, 2009;Chezem et al, 2017;Barco et al, 2019b) and suppressing TFs involved in growth and development (Lozano-Durán et al, 2013;Fan et al, 2014;Malinovsky et al, 2014;Lewis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation